Miniaturized shared aperture multiband antenna for wireless biomedical applications - Abdul Rehman Chishti; Abdul Aziz; Muhammad Nawaz Abbasi; Khaled A. Aljaloud; Ali H. Alqahtani; Rifaqat Hussain (PLoS ONE, 2026)
This study presents a compact, folded dipole multiband shared-aperture antenna that operates effectively across both sub-1 and sub-6 GHz frequency bands using a single radiating structure—constructed on an FR-4 substrate. Design measures 16.40 × 10.50 × 1.52mm 3 ( 0.0386 λ × 0.0247 λ × 0.0036 λ ), ( 0.431 λ × 0.276 λ × 0.040 λ ), ( 0.512 λ × 0.328 λ × 0.048 λ ), resonates at the bands of 0.431-0.435 GHz, 4.75-4.96 GHz, and 5.64-5.88 GHz, thus having a flexibility to a wide range of applications. The proposed antenna is a folded dipole built on the upper layer, and the coaxial feeds run to horizontally and vertically oriented strips on the backside layer. This arrangement enables simultaneous use along with various frequency bands in a single physical structure by taking advantage of shared-aperture concept thereby achieving space economy and operational efficiency. By applying a miniaturization plan based on lumped element integration, the radiating system guarantees a reduction of 80% in the dimensionality, and remains functionally intact. Besides, the integrated measurement subsystem incorporates a cancer-related analyte which mimics the electromagnetic nature of cancerous cellular organisms and thus a detectable spectral change at 5.7 GHz. The implication of this phenomenon is the initiation of an oncogenic presence diagnostic indicator. The concomitant capability of operating in multiple bands and smaller footprint make the antenna especially favourable to use in the context of operating in healthcare infrastructures for biomedical platforms along with wireless communication applications.